Climate and vegetation and their impact on stable C and N isotope ratios in bat guano - Reid, Rachel E. B.; Waples, James T.; Jensen, David A.; Edwards, Christine E.; Liu, Xinyi (Frontiers in Ecology and Evolution, 2022)
Cave guano deposits represent a relatively untapped paleoecological archive that can provide information about past vegetation, climate and bat diet over several millennia. Recent research suggests that carbon isotope values (δ13C) measured in guano accumulations from insectivorous bats reflect the relative abundance of C3 and C4 plants on the landscape while nitrogen isotope values (δ15N) may reflect precipitation amount. Together, these proxies can provide useful information for restoration practitioners seeking to understand how plant species composition has changed over time in relation to climate and land use. To better calibrate these proxies for use in restoration, we compared instrumental records of precipitation and satellite imagery of vegetation with isotope values measured in modern bat guano from Mary Lawson Cave, a large limestone cavern located in central Missouri. Mary Lawson Cave hosts a maternity colony of insectivorous gray bats (Myotis grisescens) and as such, contains significant guano accumulations. In fall of 2018, we collected a 60 cm long guano core that dates to 1999 cal AD at its base. Guano core δ13C values decrease from the base toward the surface (from ~-26 to -27 ‰) whereas δ15N values increase toward the surface even after accounting for ammonia volatilization (from ~3 to 5 ‰). Presently, the landscape around Mary Lawson Cave is dominated by deciduous forest and pasture. Given that land cover has changed very little over this period, the decline in δ13C values toward the present likely reflects a shift in land management on farms and/or increases in invasive C3 species. Rainfall amounts from nearby Lebanon, Missouri are significantly positively correlated with guano ẟ15N values, a relationship that is notably opposite that observed previously in soil and plants. We argue that heavy fertilizer application and significant grazing intensity could lead to the accumulation of large pools of excess, labile nitrogen which would be vulnerable to leaching during precipitation events. The relationship between guano δ15N values and precipitation may differ for materials from less agriculturally impacted locations or time periods and should be extended into the past with caution.